Religion and Narration of Covid-19 on Social Media: A Study on Dapur Narasi Social Movement - Choironi, M. Alvin Nur (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
This article aims to analyze the social movements carried out by Dapur Narasi in fighting against misleading religious information about Covid -19. Data were collected from various online media, especially the Dapur Narasimedia, social media, and personal interviews. The finding indicates that at the beginning of the emergence of COVID- 19 in Indonesia, there were many false religious narratives, both from online media and the Islamic preachers. This article shows that the identity paradigm also creates a counter-narrative movement initiated by Dapur Narasi is carried out not only by its own members but also by other figures or communities who hold the same values. This is the reason why the narration raised by Dapur Narasi reach a large number of people.